Identification of anthocyanin pigments in strawberry (cv Camarosa) by LC using DAD and ESI-MS detection - Lopes-da-Silva, M.F. (2011)
New high performance liquid chromatography (HPLC) conditions were developed for the separation of strawberry anthocyanins that provided a good resolution of peaks at a low flow rate compatible with the requirements of the mass spectrometry (MS) detector. A strawberry extract was fractionated by column chromatography and simple fractions containing basically anthocyanins were obtained, making their analysis by HPLC possible using on-line photodiode array detection and MS. Information on the identity of the major and some secondary anthocyanins in strawberry was obtained froth their retention characteristics, UV-visible spectra and mass spectra. The presence in strawberry of the previously reported cyanidin 3-glucoside, pelargonidin 3-glucoside, pelargonidin 3-rutinoside and pelargonidin 3-acetylglucoside was confirmed and cyanidin 3-rutinoside was identified in strawberry for the first time. Furthermore, cyanidin 3-malonyldiglucoside, pelargonidin 3-malylglucoside, a pelargonidin bioside and two possible pelargonidin 3-biosides acylated with acetic acid were also tentatively assigned.